The THE SOUND OF SILENCE: THE BARRIERS ON STUDENTS’ ORAL PARTICIPATION IN THE CLASSROOM - GARINGAN, ELEANOR (IJRDO- Journal of Educational Research, 2021)
There are many reasons to believe that classroom interaction or students’ oral participation in class is a necessity and beneficial for learners. However, getting students to respond is not always the situation in many classes. In Quirino State University, oral participation is one of the problems that most teachers face. The qualitative inquiry method was used. Data were collected through individual interviews, focus group discussion, classroom observations, and relevant document used in this study. Narrative analysis was utilized and purposeful sampling technique was used. Data were analyzed using Hyper Research. The findings suggest that the participants’ classroom participation experiences were influenced by multiple factors, the major ones include inferiority complex, social phobia or fear, period of adjustment, no self-esteem and not customary to speak in class. With these findings, the researcher recommends, student-centered approach, provide friendly classroom, use innovative teaching strategies, ensure that all students have equitable opportunities to learn and to perform to a standard, and help students acquire social skills needed to interact effectively.